P. Papini Stati Thebaidos libri XII - Statius, P. Papinius (Mnemosyne, Supplements, 1996)
This is a reprint of an edition first published in 1983. It includes a list of corrections which have come to light since then. The edition includes a Praefatio which sheds light on the relationship between the major manuscripts; there is also a full apparatus which reports the significant readings from fresh collations of the major manuscripts, and established a text based on a full account, with discussion where necessary, of all important suggestions published before 1980 or suggested privately to the editor. It also includes an appendix which lists all variant readings known to the editor but which are unlikely to be helpful in establishing a text. The edition will be the starting point for any serious work on the epic.